Linearly weighted classifier circuit - Yıldız, Merih; Minaei, Shahram; Özoğuz, Serdar; Özoğuz, İsmail Serdar (IEEE, 2009)
In this paper a CMOS realization of a linearly weighted classifier circuit which is called classifier block is proposed. The proposed classifier block is composed of Linearly Weighted Circuits (LWC) and CMOS Core Circuits (CC). The proposed circuit can classify linearly non-separable data. The weights of the classifier circuit are achieved with LWC blocks. Using 0.35 μm AMS technology parameters, SPICE simulation results for a LWC and classifier block are included to verify the expected results.
Keywords: CMOS Integrated Circuits; Linear Network Analysis